α-Synuclein Negatively Regulates Nurr1 Expression Through NF-κB-Related Mechanism - Jia, Congcong; Qi, Hongqian; Cheng, Cheng; Wu, Xuefei; Yang, Zhaofei; Cai, Huaibin; Chen, Sheng; Le, Weidong (Frontiers in Molecular Neuroscience, 2020)
The nuclear receptor related 1 protein (Nurr1) is critical for the development and survival of midbrain dopamine neurons that are predominantly affected and progressively degenerated in Parkinson’s disease (PD). The expression level of Nurr1 has been proposed to be modulated by α-synuclein (α-SYN), an important pathological hallmark of PD. However, the underlying molecular mechanisms of α-SYN-Nurr1 interaction are still rarely explored. In this study, we investigated the effect and mechanism of α-SYN on the transcription level of Nurr1. Our results showed that overexpression of α-SYN (WT or A53T) reduced Nurr1 and its downstream genes expressions. α-SYN neither affected the mRNA stability nor bound with the promoter of Nurr1, but modulated the transcription activity of Nurr1 promoter region ranged from -605 bp to -418 bp which contains the binding site of nuclear factor kappa B (NF-κB). Moreover, overexpression of α-SYN (WT or A53T) down-regulated NF-κB expression level, thereby inhibiting the transcription factor activity of NF-κB and decreasing the binding quantity of NF-κB with Nurr1 promoter. These findings may give us new insights to better understand the molecular mechanisms underlying the α-SYN-regulated Nurr1 function, which may fascinatethe investigation of dopamine neuron degeneration in PD pathogenesis.